Mobile forensic extraction tool / Nur Aqilah Sarbaini - Sarbaini, Nur Aqilah (2019)
Recently, as we can see everybody in this world used smartphone as a medium that can be replace a computer to a handy devices to send text messages, make a voice or video call, take a picture, record a video, playing games, connect to the internet, and many more. There are plenty of mobile architecture offered in the market such as iOS, Android, Blackberry, Windows Phone, Symbian, and others. According to Brian Barrett (2018), the moment user clicked the wrong link; the mobile phone will easier to be vulnerable and might be the target of crime or be source of crime. Although, there are many existing tools available, it is expensive and this poses a major challenge to forensic investigator and law enforcement to handle a case. In this project, tool is developed to extract the evidence from the mobile devices.